Not all rare species are the same: contrasting patterns of genetic diversity and population structure in two narrow‐range endemic sedges. (23rd January 2015) - Binks, Rachel M.; Millar, Melissa A.; Byrne, Margaret
<x xml:space="preserve">Abstract</x> The many spatial and temporal configurations in which species can be classified as rare may result in various genetic signatures, despite a persistent generalization that populations of rare species are genetically depauperate and highly differentiated. We assessed genetic diversity and differentiation in two narrow endemics with contrasting geographical distributions using 12 nuclear and six chloroplast microsatellite loci. Consistent with both marker types, the smaller, more isolated Lepidosperma sp. Parker Range populations were characterized by lower diversity and stronger divergence, relative to higher diversity and extensive connectivity among the geographically clustered L. sp. Mt Caudan populations. However, neither species exhibited low diversity, despite high inbreeding. Together, our results suggest that these species are naturally rare and have long persisted in this landscape while maintaining genetic diversity and tolerating considerable inbreeding. Their resilience is probably due to large population sizes and the flexibility afforded by employing sexual and asexual reproduction. Their contrasting genetic dynamics demonstrate that not all rare species share generalized patterns, even within the same rarity category. Moreover, these patterns were better predicted by fine‐scale descriptors of rarity, population size and distribution, rather than the more typically used geographical range. This study highlights the complex dynamics of rare species and cautions against using broad assumptions to classify and manage rare species. © 2015 State of Western Australia, Biological Journal of the Linnean Society, 2015, 114, 873–886.